Canadian Helicobacter Study Group Consensus Conference: Update on the Management of Helicobacter pylori - An Evidence-Based Evaluation of Six Topics Relevant to Clinical Outcomes in Patients Evaluated for H pylori Infection. (1st September 2004) - Hunt, Richard; Fallone, Carlo; Veldhuyzan van Zanten, Sander; Sherman, Phil; Smaill, Fiona; Flook, Nigel; Thomson, Alan; all participants of CHSG 2004,
Abstract : As an update to previously published recommendations for the management of Helicobacter pylori infection, an evidence-based appraisal of six topics was undertaken in a consensus conference sponsored by the Canadian Helicobacter Study Group. The issues addressed and recommendations made were: bismuth-containing quadruple therapy is appropriate as an alternative first-line eradication strategy for H pylori infection; searching for and treating H pylori infection is warranted in patients considered to be at high risk for gastric cancer; H pylori infection should be eradicated before initiating long-term treatment with nonsteroidal anti-inflammatory drugs or acetylsalicylic acid; the stool antigen test has a limited role in the diagnosis of H pylori infection; the benefits of H pylori eradication in patients on long-term proton pump inhibitor therapy are not sufficient to warrant recommending a strategy of searching for and eradicating the infection among these patients; and a strategy of 'test and eradicate' for H pylori infection in patients with uninvestigated dyspepsia is cost-effective in Canada relative to a trial of proton pump inhibitor therapy. The goal was to establish guidelines on the best evidence using the same structure to address and formulate recommendations for each issue. The degree of consensus for each issue is presented.